2018
DOI: 10.1017/s1463423618000294
|View full text |Cite
|
Sign up to set email alerts
|

A study to evaluate the effectiveness of Best Beginnings’ Baby Buddy phone app in England: a protocol paper

Abstract: We will use a mixed-methods approach, a cohort study, a qualitative element and analysis of in-app data. Participants will be first-time pregnant women, aged 16 years and over, between 12 and 16 weeks of gestation and recruited from five English study sites.Evaluation planWe will compare maternal self-efficacy and mental health at three months post-delivery in mothers who have downloaded the Baby Buddy app compared with those that have not downloaded the app, controlling for confounding factors. Women will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Mobile-Health (mHealth) technologies offer the potential to support traditional lifestyle interventions without increasing contact hours with clinicians (12). Smartphone apps have been proposed as a novel method to provide antenatal education, for example in improving glycaemic control (13), gestational weight gain (14,15) and maternal self-efficacy and mental wellbeing (16). A recent meta-analysis demonstrated the increasing prevalence of mHealth-supported randomized controlled trials for weight management in pregnancy (17).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile-Health (mHealth) technologies offer the potential to support traditional lifestyle interventions without increasing contact hours with clinicians (12). Smartphone apps have been proposed as a novel method to provide antenatal education, for example in improving glycaemic control (13), gestational weight gain (14,15) and maternal self-efficacy and mental wellbeing (16). A recent meta-analysis demonstrated the increasing prevalence of mHealth-supported randomized controlled trials for weight management in pregnancy (17).…”
Section: Introductionmentioning
confidence: 99%
“…Recruitment for the qualitative arm was from three maternity units participating in the main BaBBLeS study [ 10 , 11 ] (located in the Northwest, Southeast, and Midlands, England). The inclusion and exclusion criteria are listed in Textbox 1 .…”
Section: Methodsmentioning
confidence: 99%
“…This observational study assessed the effectiveness of the Baby Buddy app in improving maternal self-efficacy and mental well-being [ 10 , 11 ]. It also involved a qualitative arm that aimed to understand when, why, and how first-time mothers use the Baby Buddy app and the perceived benefits and challenges [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The app is reported to: increase parents’ confidence, skills, well-being; promote mother-infant attachment; reduce social isolation; support behaviour change (eg, one study showed a 9% increase in exclusive breast feeding) 30. However, a recent randomised controlled trial reported no impact on maternal self-efficacy 3 months postbirth, but a post hoc analysis indicated improved breast feeding at 1 month 31…”
Section: The Role Of Smartphone Technologymentioning
confidence: 99%